Penggunaan Naratif Dalam Video Game Sebagai Media Edukasi Isu Dunia: Studi Kasus Detroit Become Human - Tony Wibowo; Kelfia Limanda (Pixel :Jurnal Ilmiah Komputer Grafis, 2020)
Video games with strong narratives are getting popularity among video game developers. There are a number of games that were developed with world issues as the narrative. This research was conducted to prove whether a video games have a potential to be a media for education on world issues. This research was conducted by exposing video games through game play video of Detroit Become Human video game to 27 respondents who are not familiar with said video game for 22 days and submit their report about their experience through online questionnaire. The study was tested by comparing the respondents' views on the world's issues before and after the respondents exposed to the video and codifying their responses in order to quantify the responses received. The results of the study prove that the consensus agrees that video games have the potential to be a media for education on world issues. Apart from that, it was also found that video games were able to educate players in the long term but not significant in the short term.